Effects of microbial communities during the cultivation of three salt-tolerant plants in saline-alkali land improvement - Wang, Yijun; Gong, Huarui; Zhang, Zongxiao; Sun, Zeqiang; Liu, Shenglin; Ma, Changjian; Wang, Xuejun; Liu, Zhaohui (Frontiers in Microbiology, 2024)
Planting vegetation on saline-alkaline land enhances soil fertility and sustainability by improving salt-alkali tolerance. Different salt-tolerant plant species interact with soil microorganisms, enriching bacterial communities and promoting nutrient availability. In this study, mechanisms affecting microbial communities in severely saline-alkaline soils planted with salt-tolerant plants are investigated. Over 4 years, the potential to cultivate three salt-tolerant plant species (tall wheatgrass Agropyron elongatum, chicory Chicorium intybus, and alfalfa Medicago sativa) in severely saline-alkaline soils is compared with a non-cultivated control. Bacterial and fungal communities were characterized through high-throughput sequencing of the 16S rRNA gene V3–V4 region and the V4 region, respectively. Cultivating these three plant species significantly reduces soil electrical conductivity values. Chicory cultivation notably increased soil nutrients, bacterial alpha richness, and fungal alpha diversity and richness. Microbial community structures vary considerably between the control and treatments, significantly correlating with the soil quality index. This index enables an assessment of soil health and fertility by integrating variables such as nutrient content, microbial diversity, and salinity levels. In each plant treatment, particularly alfalfa, the relative abundances of fungal pathogens like Neocosmospora and Gibellulopsis increase, which may pose risks to subsequent crops such as tomatoes, requiring careful consideration in future planting decisions. Conversely, in alfalfa and tall wheatgrass treatments, there was an increase in the relative abundances of fungal genera (e.g., Alternaria and Podospora) that antagonize fungal pathogens, while Paraphoma increased in the chicory treatment. The strong relationship between microorganisms and the rise in pathogen-resistant fungi across different plant treatments highlights robust and beneficial structural characteristics. According to soil quality index scores, each treatment, but especially that of chicory, improved the severely saline–alkaline soil environment.